EFFECT OF FEEDING WITH HERB OF ERYTHRINA VARIEGATA TO BIOCOMPATIBILITY OF THE COCOON FIBER OF WILD SILK MOTH ATTACUS ATLAS FOR FUTURE APPLICATION AS BIOCOMPATIBLE OF SILK SUTURES - Nindhia, Tjokorda Sari; Nindhia, Tjokorda Gde Tirta; Surata, I Wayan; Knejzlik, Zdenek; Ruml, Tomas (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objectives: Silk is biocompatible as biomaterial and has been used commercially as sutures. More interesting properties of the silk are that the mechanical properties exceed all natural polymer and synthetic materials. In this research, a type of silk suture is being developed from species of Attacus atlas to obtain better biocompatible sutures. A. atlas is a species of silk moth that consume not only single types of leaves. The Quality of cocoon fiber then can be arranged base on the types of the leaves that is consumed. Better biocompatibility sutures comparing with recent commercial silk sutures which is not biocompatible, can be achieved by feeding with variety types of leaves. Silk suture that already established in the market is a base product of Bombyx mori species of silk which is only consume one type of leaf (mulberry leaves). Methods: In this research, the A. atlas cocoon was produced by feeding with herb Erythrina variegate. The microstructure was observed, element composition as well as biocompatibles properties was investigated. Results: A high composition of kalium (K) as well as chloride (Cl) is identified in the fiber. The released fiber from cocoon also indicates high biocompatibility that is promising as biocompatible suture. Conclusion: The biocompatible fiber for future application as sutures is possible to be prepared by feeding the wild silkworm of A. atlas with leaf of E. variegate. The fiber is found rich with kalium (K) as well as chloride (Cl) with irregular shape of crystal at the surface of the fiber.